Relationship of Body Mass Index with Chronic Pain after Breast Surgery in Women with Breast Cancer - Majid Montazer; Zahra Hadadi; Zahra Ghavami; Mehdi Khanbabaei Gol (Mashhad University of Medical Sciences, 2019)
Introduction: Awareness of prevalence of chronic pain after breast cancer surgery and possible contributing factors in the continuation of pain after breast cancer treatment is essential in preventing this pain in improving the quality of life in patients with breast cancer. Therefore, this study was performed with aim to determine the relationship between BMI and chronic pain after breast surgery in women with breast cancer. Methods: This descriptive-correlational study was conducted on 170 patients who had inclusion criteria in Tabriz hospitals from 2017 to 2018. VAS checklist was used to measure the intensity of postoperative chronic pain over six months and a checklist of chronic risk factors affecting chronic pain for research purposes. Data were analyzed by SPSS software (version 22) and Independent t-test, ANOVA, Chi-square and Fisher tests. P<0.05 was considered statistically significant. Results: The results indicated that chronic pain at all levels was associated with increased BMI, so that with increasing BMI, the chronic pain was also increased (P <0.001) Conclusion: High BMI can be a risk factor for chronic pain after breast cancer surgery and attention to this index can be helpful in predicting chronic pain